2014
DOI: 10.1002/bies.201300113
|View full text |Cite
|
Sign up to set email alerts
|

A paternal environmental legacy: Evidence for epigenetic inheritance through the male germ line

Abstract: Literature on maternal exposures and the risk of epigenetic changes or diseases in the offspring is growing. Paternal contributions are often not considered. However, some animal and epidemiologic studies on various contaminants, nutrition, and lifestyle-related conditions suggest a paternal influence on the offspring’s future health. The phenotypic outcomes may have been attributed to DNA damage or mutations, but increasing evidence shows that the inheritance of environmentally induced functional changes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
303
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(305 citation statements)
references
References 141 publications
(191 reference statements)
1
303
0
1
Order By: Relevance
“…An analysis of semen from infertile men has shown that 14.4% of anomalous patriarchal methylation occurred in H19 and gene trap locus 2 gene (93)(94)(95). In spermatozoa from oligozoospermic men, the occurrence of hypermethylation at several maternal DMRs or hypomethylation of H19 and intergenic-DMR was increased, particularly in patients with ejaculation volumes of <10x10 6 /ml (96)(97)(98)(99). In men with oligoasthenoteratozoospermia, methylation was markedly reduced at all CpGs, reaching statistical significance in subgroups with a sperm concentration of <10x10 6 /ml.…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 99%
“…An analysis of semen from infertile men has shown that 14.4% of anomalous patriarchal methylation occurred in H19 and gene trap locus 2 gene (93)(94)(95). In spermatozoa from oligozoospermic men, the occurrence of hypermethylation at several maternal DMRs or hypomethylation of H19 and intergenic-DMR was increased, particularly in patients with ejaculation volumes of <10x10 6 /ml (96)(97)(98)(99). In men with oligoasthenoteratozoospermia, methylation was markedly reduced at all CpGs, reaching statistical significance in subgroups with a sperm concentration of <10x10 6 /ml.…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 99%
“…Thus, relative to individuals with the wild-type MTHFR 677CC genotype, those with the TT genotype have lower levels of genomic DNA methylation (57). In mice, sperm hypomethylation has been shown to increase disease susceptibility in the offspring (58), and there is growing evidence from human studies that paternal folate status can affect metabolic gene expression in the offspring through epigenetic mechanisms involving chromatin packaging in sperm (59,60). Such mechanisms may explain our findings for paternal MTHFR 677C>T, but it is not clear why similar overall associations were not seen with the child's or mother's genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Chez le lapin, une alimentation maternelle enrichie en lipides est associée à des changements d'expression de gènes dans l'embryon et à une accumulation de gouttelettes lipidiques dans le trophoblaste du blastocyste, retrouvée, en fin de gestation, dans le placenta (d'origine trophoblastique) [29]. Récemment, la notion de transmission paternelle, non génétique, de pathologies à long terme a émergé [30]. Les premières observations ont été réalisées dans des modèles animaux.…”
Section: Impact Des Biotechnologies De La Reproduction Sur La Santé Dunclassified